2003
DOI: 10.7202/006903ar
|View full text |Cite
|
Sign up to set email alerts
|

Unions and Pay Equity Bargaining in Canada

Abstract: Au cours des années 1980, un certain nombre de gouvernements provinciaux ont introduit des politiques pro-actives d’équité salariale afin de concrétiser d’une manière plus efficace le principe d’un salaire égal pour un travail de valeur comparable. On a fait adopter des lois couvrant le secteur public au Manitoba, en Ontario, à l’Île-du-Prince-Édouard, en Nouvelle-Écosse et au Nouveau-Brunswick, mais la mise en place s’est également effectuée par la négociation collective initiée par le gouvernement, par exemp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 11 publications
0
24
0
Order By: Relevance
“…Further institutional roles are union advocacy to protect legal rights or joint union-management development of policy in organized workplaces, primarily but not limited to, collective bargaining, as in Dickens' advocacy of ''social regulation' ' (1999, p. 14). The labor movement's record on women's equality has been uneven in the past in Britain (Rubery and Fagan, 1995) and in Canada (Kainer, 1998), but research has shown that they have acted as a positive force for change both in the U.K. (Bewley and Fernie, 2003) and in Canada (Hart, 2002a). For example, based on case studies of pay equity bargaining in the Ontario public service and health care in Newfoundland and Labrador, Canada, the most effective unions supplemented their conventional negotiating techniques with gender analysis and pay equity expertise to gain significant wage adjustments for women (Hart, 2002a).…”
Section: Self-regulation Corporate Social Responsibilitymentioning
confidence: 97%
See 1 more Smart Citation
“…Further institutional roles are union advocacy to protect legal rights or joint union-management development of policy in organized workplaces, primarily but not limited to, collective bargaining, as in Dickens' advocacy of ''social regulation' ' (1999, p. 14). The labor movement's record on women's equality has been uneven in the past in Britain (Rubery and Fagan, 1995) and in Canada (Kainer, 1998), but research has shown that they have acted as a positive force for change both in the U.K. (Bewley and Fernie, 2003) and in Canada (Hart, 2002a). For example, based on case studies of pay equity bargaining in the Ontario public service and health care in Newfoundland and Labrador, Canada, the most effective unions supplemented their conventional negotiating techniques with gender analysis and pay equity expertise to gain significant wage adjustments for women (Hart, 2002a).…”
Section: Self-regulation Corporate Social Responsibilitymentioning
confidence: 97%
“…The labor movement's record on women's equality has been uneven in the past in Britain (Rubery and Fagan, 1995) and in Canada (Kainer, 1998), but research has shown that they have acted as a positive force for change both in the U.K. (Bewley and Fernie, 2003) and in Canada (Hart, 2002a). For example, based on case studies of pay equity bargaining in the Ontario public service and health care in Newfoundland and Labrador, Canada, the most effective unions supplemented their conventional negotiating techniques with gender analysis and pay equity expertise to gain significant wage adjustments for women (Hart, 2002a). Moreover, union engagement enhances the likelihood of moving beyond the business case to an alternative discourse of fairness or ethics, as well as locating the equality debate in mainstream industrial relations rather than seen primarily as a management prerogative, making real organizational change more probable (Dickens, 1999).…”
Section: Self-regulation Corporate Social Responsibilitymentioning
confidence: 97%
“…The PEe has been proactive in advising and helping employers to understand their obligations under the Act with the evaluations (pEe, 2009). In unionized workplaces, separate plans are required for different bargaining units and the union must be involved in the process (Hart, 2002).…”
Section: Findings/resultsmentioning
confidence: 99%
“…However, it is not always recognized because it is often seen as natural to women (Chung et al, 2000), consistent with a domestic ideology still evident in the workplace, and reinforced by a sexually segregated labour market (Hart, 2002). As noted by Bolton (2005: 183), for many people 'nurses represent the cultural construction of a "good woman", kind, caring and protective'.…”
Section: Nurses' Health Safety and Well-beingmentioning
confidence: 99%